GenAI image creation in EFL: prompt writing as an emerging writing activity for sustainability-focused artivism - Ata, Murat; Kunt, Naciye (Routledge Journals, Taylor & Francis Ltd, 2025)
Purpose: This study examines an intervention whose primary aim is to advance sustainability awareness (issues framed by the UN's Sustainable Development Goals) through artivism-oriented language practice tasks (art aimed at social or environmental action), and whose secondary aim is to offer purposeful English prompt-writing practice with near-immediate feedback in the form of generated images. Methodology: A qualitative descriptive study was conducted at a university in Northern Cyprus. Twenty-one preparatory-year students attended two workshops: one on sustainability and artivism, the other on prompt writing for AI image generation. Participants created 84 Generative Artificial Intelligence (GenAI) images on self-selected sustainability themes for a public World Environment Day exhibition. Data comprised participants' written prompts, descriptive texts, researchers' field notes, and semi-structured interviews with 15 participants who completed the whole cycle. All sources were subjected to a thematic analysis. Findings: Learners described iterative prompt-writing practice as requiring precise wording (e.g. lexical choice, prepositions, clause structure) and reported increased confidence in writing. Artivist image generation triggered a strong cognitive-emotional reaction toward glocal sustainability challenges. Collaboration, peer revising of English phrasing, and joint troubleshooting of AI outputs emerged as pivotal mediators. Participants described these practices as transferable to future language use. Originality: This empirical study systematically investigates prompt-writing-driven GenAI artivism in an EFL setting, documenting enhanced sustainability awareness and reported gains in writing confidence and strategy use. It offers a replicable workshop-plus-exhibition model that integrates GenAI into language practice within Education for Sustainable Development.
Keywords: Generative artificial intelligence; language education for sustainable development; artivism; prompt writing; human-computer co-creativity